Oroxylin a Attenuates Limb Ischemia by Promoting Angiogenesis via Modulation of Endothelial Cell Migration - Zhang, Lusha; Chen, Lu; Li, Chunxiao; Shi, Hong; Wang, Qianyi; Yang, Wenjie; Fang, Leyu; Leng, Yuze; Sun, Wei; Li, Mengyao; Xue, Yuejin; Gao, Xiumei; et al. (Frontiers in Pharmacology, 2021)
Oroxylin A (OA) has been shown to simultaneously increase coronary flow and provide a strong anti-inflammatory effect. In this study, we described the angiogenic properties of OA. OA treatment accelerated perfusion recovery, reduced tissue injury, and promoted angiogenesis after hindlimb ischemia (HLI). In addition, OA regulated the secretion of multiple cytokines, including vascular endothelial growth factor A (VEGFA), angiopoietin-2 (ANG-2), fibroblast growth factor-basic (FGF-2), and platelet derived growth factor BB (PDGF-BB). Specifically, those multiple cytokines were involved in cell migration, cell population proliferation, and angiogenesis. These effects were observed at 3, 7, and 14 days after HLI. In skeletal muscle cells, OA promoted the release of VEGFA and ANG-2. After OA treatment, the conditioned medium derived from skeletal muscle cells was found to significantly induce endothelial cell (EC) proliferation. OA also induced EC migration by activating the Ras homolog gene family member A (RhoA)/Rho-associated coiled-coil kinase 2 (ROCK-II) signaling pathway and the T-box20 (TBX20)/prokineticin 2 (PROK2) signaling pathway. In addition, OA was able to downregulate the number of macrophages and neutrophils, along with the secretion of interleukin-1β, at 3 days after HLI. These results expanded current knowledge about the beneficial effects of OA in angiogenesis and blood flow recovery. This research could open new directions for the development of novel therapeutic intervention for patients with peripheral artery disease (PAD).